Effects of Intercept pathogen reduction treatment on extended cold storage of apheresis platelets. Issue 1 (8th December 2020) - Agey, Alisa; Reddoch‐Cardenas, Kristin; McIntosh, Colby; Sharma, Umang; Cantu, Carolina; Cap, Andrew; Bynum, James
Abstract: Background: Platelets pose the greatest transfusion‐transmitted infectious risk among blood products. Refrigeration of platelets can mitigate bacterial contamination and extend platelet shelf life. Implementation of pathogen reduction technologies (PRTs) at blood banks has become increasingly popular to protect against emerging and reemerging infectious diseases. In this study, we sought to evaluate the effects of Intercept PRT on platelets collected on different platforms and cold‐stored for up to 21 days in plasma and platelet additive solution (PAS). Methods: Double‐dose apheresis platelets were collected with use of a Trima or Amicus system into either 100% plasma or 65% InterSol PAS/35% plasma and split equally between two bags. One bag served as control, while the other received Intercept PRT treatment. Bags were stored unagitated in the cold and evaluated on Days 1, 7, 14, and 21 to assess platelet metabolism, activation, aggregation, and clot formation and retraction. Results: By Day 14 of storage, lactate levels reached approximately 13 mmol/L for all samples irrespective of Intercept treatment. Mean clot firmness dropped from the 62.2‐ to 67.5‐mm range (Day 1) to the 28.4‐ to 51.3‐mm range (Day 21), with no differences observed between groups. Clot weights of Intercept‐treated Trima/plasma samples were significantly higher than control by Day 14 of storage ( P = .004), indicating a reduced clot retraction function. Intercept treatment caused a higher incidence of plasma membrane breakdown in plasma‐stored platelets ( P = .0013; Trima/plasma Day 14 Control vs Intercept). Conclusions: Intercept treatment of platelets and subsequent cold storage, in plasma or PAS, results in comparable platelet metabolism platelets for up to 14 days of storage but altered clotting dynamics. Pathogen‐reduced platelets with an extended shelf life would be beneficial for the deployed setting and would greatly impact transfusion practice among civilian transfusion centers.